Coagulase production by strains of Staphylococcus aureus of differing resistance characters: a comparison of two traditional methods with a latex agglutination system detecting both clumping factor and protein A. Issue 4 (April 1986) - Dickson, J I; Marples, R R
Abstract : Five groups of strains of Staphylococcus aureus (54 in total) were tested by slide and tube coagulase methods with rabbit and human plasma, and the results were compared with a latex test for both clumping factor and Protein A (Staphaurex, Wellcome Foundation). The five groups comprised: epidemic methicillin resistant S aureus (group 1); other methicillin resistant S aureus (group 2); other resistant S aureus (group 3); other S aureus (group 4); and a group of reference strains, not all true S aureus (group 5). Groups 1, 3, and 4 gave consistently strong positive results with the tube test and the latex test and less strong positive results with the slide test. Group 2 strains sometimes gave weak or negative results in slide and latex tests, but tube tests with both types of plasma were strongly positive. Only within group 5 strains were negative results in the tube test found. Group 1 strains showed no diminution in expression of free coagulase or of clumping factor. The latex test was more sensitive than the slide test but less sensitive than the tube test. Doubtful or negative slide test or latex test results, particularly with strains resistant to methicillin, should be checked by a tube coagulase test.